2012
DOI: 10.1128/jvi.00551-12
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Classical Swine Fever Virus with Enhanced Pathogenicity Reveals Synergistic Virulence Determinants in E2 and NS4B

Abstract: c Classical swine fever virus (CSFV) is the causative agent of classical swine fever (CSF), a highly contagious disease of pigs. There are numerous CSFV strains that differ in virulence, resulting in clinical disease with different degrees of severity. Low-virulent and moderately virulent isolates cause a mild and often chronic disease, while highly virulent isolates cause an acute and mostly lethal hemorrhagic fever. The live attenuated vaccine strain GPE ؊ was produced by multiple passages of the virulent AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 55 publications
2
74
0
Order By: Relevance
“…8). This suggests that the virulence of CSFV is more likely a multi-genic trait determined by a complex interplay of several viral proteins or genes acting in concert as already postulated in previous studies (Leifer et al, 2013;Tamura et al, 2012). To the best of our knowledge, this is the first study to show that the N-terminal domain of CSFV NS4B can confer enhanced pathogenicity to a low virulent virus, which was related to an enhanced viral replication.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…8). This suggests that the virulence of CSFV is more likely a multi-genic trait determined by a complex interplay of several viral proteins or genes acting in concert as already postulated in previous studies (Leifer et al, 2013;Tamura et al, 2012). To the best of our knowledge, this is the first study to show that the N-terminal domain of CSFV NS4B can confer enhanced pathogenicity to a low virulent virus, which was related to an enhanced viral replication.…”
Section: Discussionsupporting
confidence: 68%
“…The CSFV genome and the viral proteins N pro , E2 and NS4B of the GPE 2 vaccine strain and of the highly virulent Eystrup strain are depicted schematically. The amino acid differences related to virulence reported previously (Tamura et al, 2012(Tamura et al, , 2014 and the five additional residues in the N-terminal half of NS4B (2377, 2391, 2398, 2399 and 2414) evaluated in the present study (#) are shown. Numbering starts with the methionine encoded by the AUG start codon.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations